Discharging ear and facial palsy: Clinical presentation of metastatic follicular carcinoma of thyroid in temporal bone- a case report (Bangladesh Journal of Otorhinolaryngology, 2013)
Follicular carcinoma of thyroid spreads more through haematogenous route rather than lymphatic route. Distant metastasis usually occurs to lung and bones. In the skull, metastasis usually occurs in occipital bone. Metastasis to temporal bone is a rare event. A 45 years female patient presents with discharging ear and facial palsy which was proved to be a metastatic follicular carcinoma in temporal bone. Total thyroidectomy and excision of secondary in temporal bone were done. After surgery she had radio iodine ablation. She was well when last followed up 6 months after surgery. DOI: http://dx.doi.org/10.3329/bjo.v19i1.10738 Bangladesh J Otorhinolaryngol 2013; 19(1): 65-68